Pengaruh Perendaman Alkali, Kalium Permanganat, dan Hidrogen Peroksida terhadap Perubahan Diameter Serat Sabut Kelapa Sebagai Bahan Komposit Ramah Lingkungan - Arsyad, Muhammad; Soenoko, Rudy (INTEK: Jurnal Penelitian, 2019)
This study aims to determine the effect of alkali treatment and hydrogen peroxide on the change in diameter of coconut fiber as an environmentally friendly composite material. This research was carried out with several stages, namely: preparation of materials and tools, treatments, measurement of diameter, analysis, and discussion. Materials and equipment used are coconut fiber, alkaline solution, hydrogen peroxide solution, distilled water, a set of immersion media, and digital microscopes. Coconut fiber was soaked in alkaline solution with 10% concentration for 1, 3, 5, 7, 9, and 11 hours, then dried in a furnace at 90oC for 5 hours. Furthermore, coconut fiber was soaked again in potassium permanganate solution with a concentration of 0.5% for 1, 3, 5, 7, 9, and 11 hours, then dried in a furnace at 90oC for 5 hours. Then the coconut fiber was soaked again in a hydrogen peroxide solution with a concentration of 10% for 1, 3, 5, 7, 9, and 11 hours, then dried in a furnace at 90oC for 5 hours. After that, using a digital microscope the diameter of coconut fiber is measured. Based on the measurement results, it was concluded that the diameter of coconut fiber was degraded in diameter after soaking in alkaline solution, potassium permanganate, and hydrogen peroxide. The highest percentage reduction in diameter was 58.08% in the third treatment.